Portfolio optimization of financial returns using fuzzy approach with NSGA-II algorithm - Jirakom Sirisrisakulchai (2018)
This paper applied possibilistic approaches to a portfolio selection model. We considered a return rate as fuzzy variables. Based on the concept of possibilistic moments of fuzzy numbers, fuzzy stock returns and market risks are quantified by possibilistic mean and lower possibilistic semivariance, respectively. The non-dominated sorting genetic algorithm II (NSGA-II) was used to obtain the pareto optimal investment strategies for the integrated oil and gas company stocks.